The worldwide setting of higher education quality enhancement activities coupled with KPIs - Rawabdeh, Ali; Anis S. Khassawneh, Rami Tubaishat, Jamal Abu-Doleh, (Opción, 2019)
This article aims at endorsing unmistakable ways of evaluating and upgrading the quality of higher education and making them basic to social and economic demands via comparative qualitative research methods. As a result, the standard of quality assurance (one of the eight quality Pillars of the local agency) committee has to advise all University units through meetings and mailings that this deficiency needs addressing, and AQAC is entrusting the modern quality administrators to focus on this issue. In conclusion, teaching and learning are the core tasks of faculty who expected to acknowledge unimaginable commitment for that work.